THE EFFECT OF CONSUMER PERCEIVED VALUE ON IMPULSIVE BUYING ON THE XIAOMI BRAND SMARTPHONE TRADING: SOCIAL INFLUENCE MODERATION EFFECT - Donny Arif; Amin Saputra (Universitas Maarif Hasyim Latif, 2022)
This study aimed to determine the direct and indirect effects of consumer perceived value on impulse buying decisions for Xiaomi brand smartphone products and the moderating effect of social influence. The population of this study was students, with a total sample of 100 people. The research method used is quantitative research with descriptive and correlational analysis techniques. Data collection was carried out by distributing Likert scale questionnaires. The statistical analysis used was frequency analysis, validity and reliability tests, classical assumption tests, moderated regression, and path analysis. Research results: 1) Consumer perceived value has a direct and significant effect on impulsive purchases. 2) Social influence has a direct and significant effect on impulse buying. 3) The interaction of consumer perceived value and social influence has no significant effect on impulsive purchases. 4) Consumer perceived value and social influence have a significant simultaneous effect on impulsive buying decisions. 5) Social influence can mediate the effect of consumer perceived value on impulsive purchases